The periculum mortis and the juridical norms of the Catholic Church regarding the Sacraments: Canonical Perspective - Daniel Ortega Galed (International Journal of Indonesian Philosophy & Theology, 2022)
In danger of death (periculum mortis), the canonical rules laid down under “normal conditions” concerning the reception and service of the Sacraments are often impossible to adhere to. One of the fundamental problems in pastoral life is a lack of juridical knowledge of the “graces, dispensations, exceptions” in canon law in situations of the danger of death, which can be detrimental to the spiritual rights of the faithful. It is, therefore, essential to examine both normatively and pastorally. Canon law seriously takes the danger of death as a matter of its positive norms. The “exegesis method” of canon law will be used in the canon on periculum mortis, especially book IV of CIC 1983. In conclusion, it is evident that in the face of the danger of death for every physical person in the Church, the principle: salus animarum suprema lex is the only norm that must be observed.